STUDI PERBANDINGAN EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL DAN TEKS DALAM PEMBELAJARAN AGAMA ISLAM MENGGUNAKAN TEKNOLOGI INFORMASI - Jannah, Suci Nurul (Proceeding International Seminar of Islamic Studies, 2023)
Education is essentially a conscious effort developing human resource potential (SDM) learners by encouraging and facilitating their learning activities. In conveying lessons, various tools have been created to make it easier for the student to understand them. The development of science and technology further encourages renewing efforts in the use of technological products in the learning process. The learning medium is an intermediary or tool used in the teaching process so that material presented is acceptable to the learner. In this regard, both print out and visual audio media play a crucial role in achieving maximum learning results. The technology in the learning of Islam will discuss how we use media and tools in the process of teaching religion, which is the skill, attitude, action, and strategy of teaching religions that are the source of the qur 'an and the hadith. In comparison the effectiveness of the learning media in the learning of Islam, that is, can be seen from that media function. The learn-based medium (print out) is a variety of learning messages from which the text (literature) and its supporting illustrations are presented. One of the learning media that is often used in the learning process is a textbook. Textbooks can encourage children to do te chores.